Les banques de données ou le défi d’une société de l’information - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1988)
In our society of information, databanks are in the core of every corporate strategy. After a brief description of the various types of databanks, the article surveys the industry and analyzes the insurance oriented databanks. As the industry is largely dominated by the United States, the author suggests that Quebec's databanks industry, possibly in accordance with the government, works out to produce profitable databanks that would help Quebec to be part of the information industry actually expanding.